Human rights' interdependence and indivisibility: a glance over the human rights to water and sanitation - Priscila Neves-Silva; Giselle Isabele Martins; Léo Heller (BMC, 2019)
Abstract Background In 1948 the Universal Declaration of Human Rights was drawn up. The content of this document was further reflected two treaties, the Covenant on Civil and Political Rights, and the Covenant on Economic, Social and Cultural Rights. To try to maintain the interrelationship between the rights contained in each document, the idea that all rights are interdependent and indivisible was stressed. Based on this vision, this study aimed to explore the extent to which the violation of the human rights to water and sanitation interferes with the guarantee of other rights, addressing the principles of interdependence and indivisibility. Methods For that, 24 homeless, in the city of Belo Horizonte, Brazil, were interviewed. Individual and group interviews were carried out in addition to participant observation. The content analysis was used in order to analyze the data collected. Results The research found that violation of the rights to water and sanitation promotes violation of other rights, such as health and education rights, strengthening the view of rights' interdependence and indivisibility. Conclusion It is important to affirm that the protection of human rights must be consolidated at an operational and normative level, aligned to concepts of indivisibility and interdependence as it has been proposed for approximately seven decades.